The orientation and oviposition choices of Plutella xylostella and its parasitoid Diadegma semiclausum on a range of Brassica plants - Ruhanen, Helena M.; Bruns, Sanne; Parsons, Julia; Kivimäenpää, Minna; Blande, James D. (Arthropod-Plant Interactions, 2025)
Plants emit volatile organic compounds (VOCs) that mediate interactions with organisms in the surrounding community, such as herbivorous insects and their natural enemies. Understanding on plant attractiveness for insects can help to design intercropping systems, such as trap crops. Here we present the results of laboratory tests designed to compare the attractiveness of cabbage (Brassica oleracea), broccoli (Brassica oleracea var. italica), turnip (Brassica rapa var. rapa), and yellow rocket (Barbarea stricta) to Plutella xylostella and its natural enemy, the parasitoid wasp, Diadegma semiclausum. Plants were selected based on the results of a cabbage intercropping field experiment and a screening of VOC emissions of a variety of landrace Brassica plants both intact and damaged by P. xylostella. Plutella xylostella selected turnip and B. stricta over cabbage and broccoli in oviposition tests. Reproductive success of Diadegma semiclausum in oviposition tests was higher on host larvae feeding on turnip plants compared to cabbage and broccoli, while B. stricta was not tested. According to principal component analyses, volatile blends emitted by turnip and B. stricta differed from each other as well as from other plants, while volatile blends emitted by cabbage and broccoli were more similar, both when intact and when damaged by P. xylostella.